Effects of surface roughness on local friction and temperature distributions in a steel-on-steel fretting contact. (April 2018) - Qin, W.; Jin, X.; Kirk, A.; Shipway, P.H.; Sun, W.
Abstract: It has generally been assumed that initial surface roughness has significant influences on local frictional shear stresses and flash temperatures in fretting contacts. However, since these hypotheses are difficult to directly measure, the frictional shear stress and temperature rise distributions in a steel-on-steel fretting contact are investigated by finite element method. The rough contacting surfaces were modelled as fractal surfaces by the Weierstrass-Mandelbrot function. The simulation results show that the frictional shear stress distribution resulted from the rough contact model is discrete, and the local stresses are highly concentrated which result in higher peak temperature rise than that from the smooth contact model. The influences of the plasticity of materials, load and frequency on the temperature rise are also discussed. Highlights: The rough contact surfaces are characterized as fractal surfaces. The FE models including the surface roughness are developed for a fretting contact. The distributions of frictional shear stress and temperature rise are investigated. The effects of plasticity, load and frequency on temperature rises are discussed.